Covalent and kinetic trapping repair machinery for structural and functional studies - Kunetsky, Vladislav; Justus Liebig University Giessen (My University, 2021)
The principal attribute of living matter is genetic information used for reproduction. Before the cell can divide, all genetic information must be reproduced without errors leading to mutations. To decrease the number of errors, a DNA mismatch repair (MMR) system must identify and repair the error. Due to the enormous length of the genome, this process must be fast and efficient. Errors can initiate apoptosis, cause tumors in higher organisms, or lead to the fixation of mutations in a population. The topic of research in these theses is the evolutionarily conserved mismatch DNA repair system from the model organism Escherichia coli, namely the initial stage of the process, which involves proteins such as MutS, MutL, MutH, and UvrD. The purpose of this work was also the development of new methods, such as single-cysteine site-specific cross-linking and Förster Resonance Energy Transfer (FRET)-based methods, to study these proteins. The primary player in such a system is MutS, which is responsible for recognizing mismatches, working with incredible accuracy. Scanning millions of nucleotides, it is able to find a single mismatch and cause a cascade reaction that will start the process of DNA repair. In this study, we investigated and reviewed in detail the mechanisms and conformational changes occurring in this protein, which are necessary for its accurate and correct operation. The structural information and site-specific single cysteine approach result in a very productive pipeline. The data obtained during this work supported the sliding clamp hypothesis of the active state of MutS and also helped to characterize several other novel transient states. In particular, ATP-induced rotation of the connector domain has been shown, as well as the inability of MutS to recruit MutL when the mismatch domain is cross-linked to DNA. The same approach was applied to another pair of proteins important for the mismatch pathway, namely, MutL and MutH cross-linking. The site-specific cross-linking with the proper design of single-cysteine variants can be used for obtaining active complexes. Furthermore, this method in the long term can give significant results for structural studies of the active MutL-MutH complex, which has not been obtained before. This strategy has previously demonstrated its power in obtaining a very important new state of MutS, namely the sliding clamp. Developing FRET-based functional methods for the binding of MutL to the DNA and MutL recruitment by MutS to the DNA, we obtained a universal and novel technology that can be used in the future to studies the kinetics and other activities of DNA interacting proteins. The fundamental knowledge acquired during conformational changes studies in combination with the fluorescent methods described above led us to the establishment of a novel, simple and robust method for checking the quality of DNA, and in particular for observing mismatches and other damages using the accumulation of fluorescent MutS.
Keywords: Mismatch repair; DNA; Cross-linking; FRET; Biosensor; MutS; ddc:570